Doing research in education theory and practice - Palaiologou, Ioanna; Needham, David; Male, Trevor (SAGE Publications Ltd, 2016)
With an impressive team of contributors, this book discusses the reality of conducting research in different educational settings and provides practical advice for both undergraduate and postgraduate students doing research in education